2015
DOI: 10.3390/e17031253
|View full text |Cite
|
Sign up to set email alerts
|

Entropic Measures of Complexity of Short-Term Dynamics of Nocturnal Heartbeats in an Aging Population

Abstract: Two entropy-based approaches are investigated to study patterns describing differences in time intervals between consecutive heartbeats. The first method explores matrices arising from networks of transitions constructed following events represented by a time series. The second method considers distributions of ordinal patterns of length three, whereby patterns with repeated values are counted as different patterns. Both methods provide estimators of dynamical aspects of short-term heartbeat signals obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Bian et al presented that OPEn could effectively distinguish young and elderly group from RRI time series [10]. Makowiec et al showed that OPEn grew systematically with age and it increased depended on gender [11]. Wejer et al [12] confirmed that OPEn reduced after the tilt compared to at rest for both vasovagal patients and healthy people groups [12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bian et al presented that OPEn could effectively distinguish young and elderly group from RRI time series [10]. Makowiec et al showed that OPEn grew systematically with age and it increased depended on gender [11]. Wejer et al [12] confirmed that OPEn reduced after the tilt compared to at rest for both vasovagal patients and healthy people groups [12].…”
Section: Introductionmentioning
confidence: 98%
“…PPEn of RRI time series can be observed that the mean value due to non-shockable ventricular arrhythmia class was higher than shockable VA class [9]. Then, the OPEn follows the PPEn was considered to deal with the equals of segments [10][11][12]. Bian et al presented that OPEn could effectively distinguish young and elderly group from RRI time series [10].…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, considerable attention has been paid to the entropy-based techniques with a very promising potential in bio-medical signal processing [8,9,10,11]. The idea of implementing the entropy notions for the measure of biodiversity is present in an increasing number of the studied biosystems, from the microscopic level [12,13] to the whole body response that can be investigated by the spectrum of electrophysiological signals as electrocardiography (ECG) [14,15,16], encephalography (EEG) [17] or magnetoencephalography (MEG) [18]. The specific values of the approximate entropy measures and their dependence on the time scales were analysed for the sEMG signals registered with patients with colorectal cancer [19].…”
Section: Introductionmentioning
confidence: 99%
“…Many measures estimating heart rate variability (HRV) have been proposed in order to quantify the regulatory function of the ANS, see [1][2][3]. Intensive healthy population studies have found a correlation between an increase in age and a decrease in many HRV indices, including indices such as RMSDD, pNN50 and HF, which are known to describe the short-term HRV (ST-HRV) [4][5][6][7][8][9][10]. Therefore, higher values of HRV have been attributed to better organization of feedback reflexes driving the organism's response to actual body needs.…”
Section: Introductionmentioning
confidence: 99%